TINGKAT PERILAKU PHUBBING PADA GENERASI Z - Watulangkow, Talita Katrin; Purbaning Tyas, Prias Hayu (Universitas Sanata Dharma, 2024)
This study was conducted with the aim of, (1) describing the level of phubbing behavior in Generation Z by students of the Guidance and Counseling study program at the Sanata Dharma University of Yogyakarta, class of 2021, and (2) proposing activity topics for the Guidance and Counseling study program based on the highest score of the item scores. Descriptive quantitative is the research method in this study. The subjects of this study were students of the Guidance and Counseling study program at the Sanata Dharma University class of 2021, who are included in Generation Z and 103 students became respondents. The level of phubbing behavior in Generation Z reviewed in this study is based on the development of the Generic Scale of Phubbing with aspect nomophobia, interpersonal conflict, self-isolation, and problem acknowledgment. The data collection techniques were carried out directly using a 52-item questionnaire. There are 46 valid items, with a Cronbach Alpha reliability index of 0,899. The result of the study revealed that: (1) there are no students who have very high level of phubbing behavior, 1 student (1%) has a level of phubbing behavior in the high category, 26 students (25,2%) have a level of phubbing behavior in the medium category, 58 students (56,3%) have a level of phubbing behavior in the low category, and 18 students (17,5%) have a level of phubbing behavior in the very low category. The results indicate that the majority of students from 2021 have low levels of phubbing behavior, they have a concern and directed focus on ongoing communication with others, without smartphones as a distraction. (2) Based on the results of the study, several activities are proposed for the Guidance and Counseling study program at Sanata Dharma University in Yogyakarta, including individual counseling and stadium general with topics such as “Phubbing and Social Bonds in Generation Z”, “Phubbing: Understanding the Psychological Aspects behind the Rise of Smartphone Use”, and “Phubbing: Interpersonal Communication Challenges in the Digital Era”.